A mobile application for STEMI care optimization: pilot implementation project report. (3rd October 2022) - Kini, A; Garcia, H; Springer, B; Vengrenyuk, A; Pineda, D; Bastone, J; Krishnamoorthy, P; Sweeny, J; Dangas, G; Gidwani, U; Ezenkwele, U; Warshaw, A; et al.
Abstract: Background: In an effort to improve outcomes of STEMI patients, we developed a secure mobile application (app) to streamline real-time communication and coordination between multiple teams taking care of STEMI patients in a large health care system. The app includes multi-level alarm and notification systems, instant EKG transmission for quick interpretation, activation of the cardiac catheterization laboratory (CCL) after expert case review, secure video chat among team members facilitating clinical discussion, continuous updates on patients' clinical status and ambulance location tracking. Purpose: One of the major shortcomings in STEMI system of care has been long delays in transfer of patients from non-PCI capable hospitals to a receiving center for primary PCI. To address the challenges of interhospital transfer, we designed a pilot project employing the app for STEMI transfer from a first contact hospital to our CCL. This report assesses the effect of the app on door-to-device time by comparing the key metric for STEMI transfer before (historic) and after app launch. Methods: The pilot project involved key leadership stakeholders from Emergency Medicine and Nursing Departments at the referring hospital, CCL and our transfer center. During pilot period (July 2021 to January 2022) the referring center activated STEMI alarms using app activation in parallel with the previously established STEMI activation process via traditional phone calls to the transfer center. The built-in workflow redundancy was introduced to ensure the rapid and efficient, and at the same time, safe and reliable response to STEMI alert. In preparation for the pilot, more than 250 people were provisioned accounts, trained on their user-specific roles and scheduled in the app according to their schedules. Results: A total of 40 suspected STEMIs were activated through the app during the pilot study; among them 30 cases were accepted for transfer and 10 rejected. After excluding patients who expired during transfer, were intubated, or had normal coronaries, final study population included 13 STEMI cases activated through the app. These cases were compared with 43 STEMIs activated through the traditional pathway from January 2019 to July 2021 before app launch. After implementing the app, the mean door-to-device time for STEMI transfer decreased from 120.3±48.3 to 91.8±15.4 min (P=0.002) (Figure 1). The significant improvement, 29 min (24%), of the key metric for interhospital transfer resulted in all STEMI cases meeting AHA goal of door-to-device time ≤120 minutes after the app launch. The respective percent of STEMI cases meeting the goal before app was 71% (Figure 2). Conclusions: Implementation of a mobile app into STEMI workflow of a large urban healthcare system had a significant impact on the quality of care for transfer of STEMI patients, which has also helped bring our clinical practice closer to the AHA guidelines pertaining to the first door-to-device time. Funding Acknowledgement: Type of funding sources: None.